2021
DOI: 10.3390/ijerph182111253
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Distressed Appearance, and Quality of Life Relate to Satisfaction with Orthognathic Surgery

Abstract: Background: In this study, we aimed to identify factors correlating with satisfaction with orthognathic surgery in order to improve its outcome. Methods: We recruited 77 participants who had received orthognathic surgery and 32 age- and gender-matched normal-controls. Questionnaires that included devised questions for family support, Big Five Inventory, Derriford Appearance Score, Pittsburgh Sleep Quality Index, Hospital Anxiety and Depression Scale, 36-Item Short-Form Health Survey, and a visual analogy scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A previous study conducted with class III DFD females showed a positive relationship between PSQI scores and temporomandibular joint degeneration [28]. Another study enrolling class II and class III DFD patients, in preparation for orthognathic surgery, suggested that lower PSQI scores were associated with higher levels of satisfaction after the surgical procedure [29]. Thus, the low sleep quality in DFD patients undergoing orthognathic surgery might be related to either functional or psychological alterations.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study conducted with class III DFD females showed a positive relationship between PSQI scores and temporomandibular joint degeneration [28]. Another study enrolling class II and class III DFD patients, in preparation for orthognathic surgery, suggested that lower PSQI scores were associated with higher levels of satisfaction after the surgical procedure [29]. Thus, the low sleep quality in DFD patients undergoing orthognathic surgery might be related to either functional or psychological alterations.…”
Section: Discussionmentioning
confidence: 96%